Rural entrepreneurship in Sinaloa, México: challenges, opportunities and their impact on economic and social development - Hernández Osuna, Adolfo Arturo (Universidad Francisco de Paula Santander, 2025)
Rural entrepreneurship in Sinaloa, Mexico faces multiple challenges, including limited access to financing, insufficient basic infrastructure, difficulties in accessing markets and lack of adequate training; however, there are numerous opportunities that, if taken advantage of, could transform the rural economy and improve the quality of life of its inhabitants, this study analyzes these challenges, opportunities and evaluates their impact on the economic and social development of the region, data was collected from surveys and interviews with rural entrepreneurs and institutional representatives, the findings reveal that rural entrepreneurship contributes significantly to employment generation, poverty reduction and social cohesion, although it is essential to implement public policies and support programs that address existing barriers and enhance identified opportunities, this article provides recommendations to promote an environment conducive to business development in rural areas of Sinaloa, Mexico